Capital Structure and the Value of Quoted Firms in Nigeria: A Test of Miller and Modigliani Irrelevant Hypothesis - Onyinyechi, Uzokwe Grace (Australian Finance & Banking Review, 2019)
This study tested an insignificant hypothesis of the capital structure of Miller and Modiglian in Nigeria. The aim was to investigate the validity of the irrelevant hypothesis. The Tobins Q market value measure was modeled as a function of debt-to-equity ratio, long-term debt to equity ratio, and retained earnings ratio. Twenty companies were selected on the basis of the information needed to conduct the survey and the availability of annual financial reports for the ten-year period 2008-2017. Cross-sectional data were obtained from the annual accounts and annual reports of the companies. Random effects were used in the analysis of fixed and random effects. The study showed that 77% volatility in market value can be predicted by the variation of independent variables in the regression model. The beta coefficient of the variables found that the debt-to-equity ratio, the long-term debt-to-equity ratio, the capital-to-earnings ratio is positively and significantly related to the market value of the selected listed companies. The study concludes that capital structure is relevant, unlike Miller’s and Modiglian’s irrelevant hypothesis. Therefore, it is recommended that managers ensure an adequate combination of capital and debt.